Primary School Teachersâ€™ and Administratorsâ€™ Opinions About Success of â€œE-Schoolâ€ Application in Turkey - Akar, Hakan; Arslan, Mehmet; Ersozlu, Zehra Nur (Mediterranean Journal of Social Sciences, 2012)
In this research that aims revealing the strong and weak points of e-school application; it has been tried to identify the views ofteachers and administrators about the success of e-school application. The research sample consists of 602 primary school teachersand administrators who are working in Tokat and its districts in Turkey. The data has been collected by a scale called â€œe-schoolapplication evaluation questionnaireâ€ which has been developed by the researchers. According to the result of the research it has beendetermined that the views of teachers and administrators on the efficacy of e-school application do not show any clear differenceaccording to the their genders, titles, their interest on computers or the location of the school; however, the teachers who are in charge ofadministration find the e-school application beneficial when compared with the other teachers. As a result of the research it has beenidentified that the views of the teachers and administrators on the usefulness of e-school application do not show any clear differenceaccording to the their genders, titles, their interest on computers or the location of the school; however, senior teachers find the e-schoolapplication useful.